Facilitators of probation-based domestic violence perpetrator programmes: ‘Who’s in the room?’ - Renehan, Nicole (Probation journal, 2021)
The role that probation practitioners play in the desistance process has begun to receive much needed attention. Yet, the experiences of facilitators of probation-based, domestic violence perpetrator programmes have long been neglected. This article explores the experiences and wellbeing of eight facilitators from one cohort of the Building Better Relationships (BBR) programme in England. Drawing upon five-months’ observations and in-depth interviews, I demonstrate how working with domestically violent men with insufficient knowledge, experience, or support, exacerbated within the context of Transforming Rehabilitation reforms, impacted significantly on facilitator well-being, professional identities, and practice. Practice implications are discussed.